2015
DOI: 10.3174/ajnr.a4267
|View full text |Cite
|
Sign up to set email alerts
|

MR Imaging–Detected Carotid Plaque Hemorrhage Is Stable for 2 Years and a Marker for Stenosis Progression

Abstract: BACKGROUND AND PURPOSE: MR imaging-detected carotid plaque hemorrhage is associated with an increased risk of recurrent ischemic cerebrovascular events and could be an indicator of disease progression; however, there are limited data regarding the dynamics of the MR imaging-detected carotid plaque hemorrhage signal. We assessed the temporal change of this signal and its impact on carotid disease progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 32 publications
1
21
0
Order By: Relevance
“…Thus, we cannot be sure whether the IPHs observed at follow-up were at the same location as those observed at baseline or if some of these may also represent newly developed IPH. In our visual assessment, however, we found that in 94% of the subjects, IPH remained present, which is in agreement with findings in two previous studies (6,24). Still, we may have underestimated the rate of new IPH development, as this would have been scored as growth of IPH with both community-dwelling subjects with atherosclerotic carotid plaques, male sex, hypertension, and current smoking were major risk factors for presence of IPH (12).…”
Section: Discussionsupporting
confidence: 80%
“…Thus, we cannot be sure whether the IPHs observed at follow-up were at the same location as those observed at baseline or if some of these may also represent newly developed IPH. In our visual assessment, however, we found that in 94% of the subjects, IPH remained present, which is in agreement with findings in two previous studies (6,24). Still, we may have underestimated the rate of new IPH development, as this would have been scored as growth of IPH with both community-dwelling subjects with atherosclerotic carotid plaques, male sex, hypertension, and current smoking were major risk factors for presence of IPH (12).…”
Section: Discussionsupporting
confidence: 80%
“…Although plaque features, such as HST1 and contrast enhancement, may persistent for months of ischemic stroke,24, 33, 34, 35 the short period (≤30 days) in our study contributed to the identification of meaningful associations of the features with culprit lesions. However, there is overlap in the studied features among groups.…”
Section: Discussionmentioning
confidence: 85%
“…As increasing evidence suggests that IPH is an undesirable pathologic event in the natural history of atherosclerosis, 15,11,12 understanding the pathogenesis and contributing factors of IPH becomes of pivotal importance. Approaches to detect and measure IPH are limited.…”
Section: Discussionmentioning
confidence: 99%
“…However, the role of IPH in atherothrombosis is becoming increasingly recognized through mechanistic prospective studies that are recently made possible by in vivo imaging. It has been recognized that IPH promotes plaque progression, 15 of which the pathways may involve iron-driven lipid oxidation, 6 cholesterol deposition from erythrocyte membrane, 7,8 blood-borne proteolytic activity, 9,10 and more. In accord with such an effect, IPH was shown in various clinical settings to predict subsequent clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%